A partial entropic lattice Boltzmann MHD simulation of the Orszag–Tang vortex. Issue 1 (1st February 2018) - Flint, Christopher; Vahala, George
ABSTRACT: Karlin has introduced an analytically determined entropic lattice Boltzmann (LB) algorithm for Navier-Stokes turbulence. Here, this is partially extended to an LB model of magnetohydrodynamics, on using the vector distribution function approach of Dellar for the magnetic field (which is permitted to have field reversal). The partial entropic algorithm is benchmarked successfully against standard simulations of the Orszag–Tang vortex [Orszag, S.A.; Tang, C.M. J. Fluid Mech. 1979, 90 (1), 129–143].